Hymenocallis ximixtlanensis (Amaryllidaceae), a new species from the state of Guerrero, Mexico - Jiménez Ramírez, Jaime; Cruz Durán, Ramiro; García Granados, Ma. Elena (Phytotaxa, 2022)
Hymenocallis ximixtlanensis is described and illustrated as a new species for science. This taxonomic entity has similarity with H. graminifolia. However, it is distinguished from the latter by presenting wider leaves (1.9–2.2(–2.8) vs. 0.5–0.7 cm), much longer floral tubes (12–14.2 vs. ca. 4 cm), longer anthers (ca. 2 vs. 1.4 cm), and ovaries with four ovules in each locule (4 vs. 2).